THE UTILIZATION OF GOOGLE ASSISTANT AS A VIRTUAL ASSISTANT IN THE SANG NILA UTAMA MUSEUM - Monika, Winda; Amelia, Vita; Hakim, Triono Dul (Community Development Journal : Jurnal Pengabdian Masyarakat, 2023)
Memory institutions which consists of galleries, libraries, archives, and museums are information management organizations that aims to documenting, contextualizing, preserving, and indexing elements of human culture. Museum is one of the memory institutions that record the traces of human civilization is in the form of a physical collection. The existence of a museum today should be a media for edutainment that can be enjoyed by all groups. The Sang Nila Utama Museum is a state museum of Riau Province which has been operating since 1975 under the auspices of the Regional Office of the Ministry of Education and Culture of Riau Province. This museum collects various kinds of collections. However, these various collections are difficult to access digitally by the public due to the limited digitization of these collections. This community services offered to develop Google Assistant as a virtual assistant to support technology that currently exists at the Sang Nila Utama Museum. Furthermore, this is an effort to attract many visitors to the museum and to seek information on the museum's digital channels. This solution hopefully could bring users to explore the museum’s collection in an exciting way.